FREKUENSI DAN INTENSITAS SERANGAN HAMA PENYAKIT PADA BIBIT MERSAWA (Anisoptera marginata Korth. ) DI PERSEMAIAN BP2LHK BANJARBARU KALIMANTAN SELATAN - Syafa’atul Aulia Zeni; Normela Rachmawati; Adistina Fitriani (Jurnal Sylva Scienteae, 2021)
Intensity and Frequency of pests disease is comparison quantity of objects be invaded and whole observed objects in percent. The intensity of pests and diseases is the level be ivaded or the level of plants damage caused by isects, fungi, bacteria or viruses that started by qualitatively or quantitalively. Pests are all animals that can be damage the trees or forest stands and forest products, plant disease is a modification or deviation in one or more parts of the physiological process and make loss of coordination in the plants.This research do in BP2LHK nursery Banjarbaru South Kalimantan from July until Semptember 2019. The method used is scoring method by determining be invaded score on mersawa seedling. The results of this study indicate that the frequency of pest and disease attacks on mersawa seedlings (Anisoptera marginata Korth) of 95.46%. The intensity of pests and diseases in the seeds of mersawa (Anisoptera marginata Korth.) of 37.9%. The level of pest damage to mersawa seedlings ranged 25,0–50,0 % include in the medium category. Keywords: Mersawa; Frequency and intensit; Pest and disease